The First 50 Years of the Journal of Research in Crime and Delinquency: An Essay. (July 2014) - Clear, Todd R.; Ho, Aaron
From its first publication in 1964–2014, 890 articles have been published by The Journal of Research in Crime and Delinquency ( JRCD ). During that period, the criminal justice field has experienced major transformations in its policies, theories, and practices. This article identifies major periods in the development of criminal justice policy; which are Prepolitical Era (1964–1972), Tough on Crime Era (1972–1980), National Consensus on Crime Policy Era (1980–1996), and Retrenchment Era (1996–2012). It then traces changes in the subject matter of JRCD over those periods. The articles published by the JRCD over the past half century reflect the changes in eras.